A review of various efforts to increase artemisinin and other antimalarial compounds in Artemisia Annua L plant - Namuli, Aidah; Bazira, Joel; Casim, Tolo Umba; Ogwang, Patrick Engeu (Cogent Biology, 2018)
The antimalarial active compounds in Artemisia annua include artemisinin, flavonoids, and aromatic oils. Artemisinin is the main antimalarial compound in A. annua, it used in the formulation of artemisinin-based combined therapies used to treat malaria. Artemisinin is largely obtained from A. annua plant but the content in it is very low and its production commercially is not cost effective worldwide. Flavonoids have a synergistic effect with artemisinin against malaria and are partly responsible for the prophylactic effect of A. annua herbal tea. Essential oils from A. annua are effective mosquito repellents. Most attempts have been made to try to raise artemisinin content. However, few or none has been tried to increase the flavonoids and aromatic oils. This article presents a review of various efforts that have been carried out to increase these antimalarial compounds
Keywords: artemisinin; biofertilizers; hormones; aromatic oils; flavonoids